2021
DOI: 10.1016/j.sjbs.2021.07.003
|View full text |Cite
|
Sign up to set email alerts
|

RAAS, ACE2 and COVID-19; a mechanistic review

Abstract: The use of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) in coronavirus disease 2019 (COVID-19) patients has been claimed as associated with the risk of COVID-19 infection and its subsequent morbidities and mortalities. These claims were resulting from the possibility of upregulating the expression of angiotensin-converting enzyme 2 (ACE2), facilitation of SARS-CoV-2 entry, and increasing the susceptibility of infection in such treated cardiovascular patients. ACE2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 63 publications
1
15
0
2
Order By: Relevance
“…Dengan pengikatan G-protein-coupled receptor Mas (Mas R), Ang 1-7 meningkatkan vasodilatasi dan memiliki efek anti-inflamasi, yang berlawanan dengan Ang II. 18,19 Peran penting dalam mengatur tekanan darah dilakukan oleh RAAS. Pengaturan tekanan darah oleh RAAS tergantung pada interaksi ACE/ANG-II/AT1R dan ACE2/ ANG-(1-7)/MasR.…”
Section: Bahasanunclassified
See 1 more Smart Citation
“…Dengan pengikatan G-protein-coupled receptor Mas (Mas R), Ang 1-7 meningkatkan vasodilatasi dan memiliki efek anti-inflamasi, yang berlawanan dengan Ang II. 18,19 Peran penting dalam mengatur tekanan darah dilakukan oleh RAAS. Pengaturan tekanan darah oleh RAAS tergantung pada interaksi ACE/ANG-II/AT1R dan ACE2/ ANG-(1-7)/MasR.…”
Section: Bahasanunclassified
“…Severe Acute Respiratory Syndrome Coronavirus-2 yang berikatan dengan ACE2 memfasilitasi fusi dan masuknya ke sel yang menunjukkan adanya interaksi langsung antara SARS-CoV-2 dan RAAS yang dapat menurunkan ekspresi ACE2 dan berakibat penurunan pembentukan Ang 1-7 yang berperan sebagai vasodilator dan meningkatnya Ang II yang berperan sebagai vasokonstriktor sehingga menyebabkan ketidak-seimbangan dalam sistem kontrol tekanan darah dan tekanan darah terus berada dalam kondisi yang tinggi. 19,20,21 Wang et al 16 melaporkan bahwa sekitar 35% pasien COVID-19 dengan hipertensi menunjukkan tekanan darah yang tidak terkontrol selama rawat inap cenderung memiliki gejala klinis lebih berat, ditunjukkan dari lebih tingginya jumlah pasien yang masuk ICU dan IMV serta lebih mungkin mengalami cedera jantung dan ginjal. Hasil penelitian Vicenzi et al 10 juga menunjukkan bahwa peningkatan tekanan darah pada pasien COVID-19 dengan hipertensi dikaitkan dengan penurunan fungsi paru.…”
Section: Bahasanunclassified
“…This pathway also reduces the harmful effects of ACE-1-Ang II-AT1 receptor axis and at the same time enhances the ACE-2 activity. As a result, ACE-2 captures the S-proteins of SARS-CoV-2 in the plasma and thus prevents the virus from binding to lung cells [ 33 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although ACE-2 expression decreases after infection by SARS-CoV-2, numerous studies suggested that ACE inhibitors and ARBs increase the expression of ACE-2 and the plasma levels of Ang (1–7) [ 35 ]. It is noteworthy that no clinical data on the effects of ARBs and ACE inhibitors on ACE-2 expression in the lungs are available in either animal or human models [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is a rapid-spreading infectious disease that emerged in Wuhan, China at the end of 2019 and was described as a global pandemic health problem by the world health organization with a remarkable impact on mortality rates and health care resources [ 1 , 2 ]. The causative virus was recognized as SARS-CoV-2 that is a member of the coronavirus β-family [ 3 ].…”
mentioning
confidence: 99%